Start-up funding at an early stage : a literature review - Vančová, Dominika; Novák, Michal; Staňková, Veronika; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2022)
Bachelor thesis analyses different options of financing available for fintech start ups at an early stage together with factors that positively or negatively influence obtaining funds from investors. This thesis conducts a systematic literature review on financing fintech start-ups. Some factors positively or negatively influence the acquisition of an investment from an investor. The author finds that some scholars are united in their findings, but some are not. Investors' prototype, proper financial reporting, correct evaluation of start-ups' worth and history with different investors are factors which scholars agree on. Contradictory results are found in deciding if start ups' location is crucial for obtaining more funding and if founders' previous experience plays a role in investors' decision making. Throughout the review, the author finds that some types of financing which came up in the search for early-stage funding should be obtained by start-ups later in their cycle.
Vedoucí práce: Michal Novák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: účetnictví a finanční řízení podniku [obor bakal. práce]; bakalářské práce; bachelor's theses